DOI: 10.31274/rtd-180813-13632
|View full text |Cite
|
Sign up to set email alerts
|

Delaying the spoilage of fresh and processed meats

Abstract: Various anti-microbial treatments were studied with respect to their use for the sheif-h'fe extension of meat and meat products. The treatments studied were bacteriocins (pediocin AcH and nisin), organic acids, immobilization, ion chelators, high pressure and irradiation. These were then compared using statistical analysis so as to identify treatment effects on the dynamics of growth of the spoilage bacteria. The experiments focused especially on exploiting the potendal of pediocin AcH for this purpose. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 216 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…Spline regression models can be used to add extra predictive data while raising the power or precision of the known predictors. In our case, the cubic Spline model is used to avoid overfitting and add precision to the model regarding various colors of RGB based upon pH values of pork loin meat from both experimental and collected data sets. , Also, Spline was used to estimate the gaps in our experimental data, while validating the estimations and/or predictions for high accuracy was derived for each color component, RGB, at an adjusted R-square of 0.888, 0.8948, and 0.6807, respectively (Tables S6–S8). To remove the gaps in data sets and meanwhile make reliable, valid estimations and predictions, the experimental and collected data at known fixed points, such as at pH 6.0 and 5.8 with associated RGB values, were estimated using the Spline technique, which allowed the flexibility between estimations but avoided the overfitting of data causing added randomness instead of precision in our food quality model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spline regression models can be used to add extra predictive data while raising the power or precision of the known predictors. In our case, the cubic Spline model is used to avoid overfitting and add precision to the model regarding various colors of RGB based upon pH values of pork loin meat from both experimental and collected data sets. , Also, Spline was used to estimate the gaps in our experimental data, while validating the estimations and/or predictions for high accuracy was derived for each color component, RGB, at an adjusted R-square of 0.888, 0.8948, and 0.6807, respectively (Tables S6–S8). To remove the gaps in data sets and meanwhile make reliable, valid estimations and predictions, the experimental and collected data at known fixed points, such as at pH 6.0 and 5.8 with associated RGB values, were estimated using the Spline technique, which allowed the flexibility between estimations but avoided the overfitting of data causing added randomness instead of precision in our food quality model.…”
Section: Resultsmentioning
confidence: 99%
“…The criteria for literature data selection include food type (pork lion,) and pH range (2.6–10), which matches the same condition as in our experimental cases. The literature data (Table S11) has been used to further strengthen our model. To obtain an accurate food spoilage classification using the sensory film colormaps and machine learning method, we identified three relevant spoilage parameters (pH, acetic acid (AA) content, and storage time (ST) representing categories pH, AA, ST).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Macronutrients, such as protein, carbonates and fat, are also not affected by doses up to 10 kGy. Sundaram (1999) employed different treatment combinations using pediocin combined with irradiation (3 kGy) and high hydrostatic pressure (HHP) (75,00 psi for 5 min) as well as other treatments to extend the shelf-life of raw and cooked lean beefsteaks. This study indicated that pediocin is tolerant to stresses of irradiation and HHP at certain levels.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…Free radicals cause extensive damage to cellular components by reacting with them. The damage to cells includes deoxyribonucleic acid (DNA) strand breaks, base damage, denaturation of proteins (Sundaram, 1999) and cytoplasmic membranes (Mendonca, 2002). Breaking bonds in DNA results in the loss of a cell's ability to replicate.…”
Section: Mechanisms Of Irradiation Inhibition On L Monocytogenesmentioning
confidence: 99%
See 1 more Smart Citation